Kajian Dinamika Universitas Al-Azhar dan Reformasi Pendidikan di Mesir serta Pengaruhnya terhadap Dunia Islam - Azmiyah, Azmiyah; Yafi, Salman; Zulmuqim, Zulmuqim; Masyhudi, Fauza (Program Studi Sejarah Peradaban Islamm UIN Raden Fatah Palembang, 2024)
Al-Azhar University is evidence of the oldest Islamic education in the world, which was founded during the Fatimid dynasty in Egypt and functions as a center for Islamic studies and a center for the spread of Isma'ili Shiite teachings. As time went by and changes in Islamic governments, the al-Azhar mosque turned into a madrasa to spread Sunni Islam and has now become a university that has produced many ulama figures who have given birth to new views and ideas for reform, thus influencing the development of education and the Islamic world throughout the world. This research aims to determine the dynamics of universities and educational reform in Egypt which have an impact on Muslims globally, including Indonesia. This research uses library research with references from books, articles and historical analysis of Al-Azhar. The results of this research are knowledge of al-Azhar from the Fatimid dynasty to the present, this motivates Muslims to continue studying and making the mosque prosperous and advancing Islamic education.